Synthesis and conformational study of the first dithia[3]metacyclo[3](2,4)pyrrolophane and [2]metacyclo[2](2,4)pyrrolophane. 1H NMR spectroscopic evidence for a novel hydrogen-bonding phenomenon - Lai, Y.-H. (2014)
Journal of Organic Chemistry